2020
DOI: 10.1038/s10038-020-00850-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of contralateral and ipsilateral breast cancers and prognosis in BRCA1/2 pathogenic variant carriers based on the Japanese HBOC Consortium registration

Abstract: This study aimed to clarify the breast cancer prognosis in Japanese patients with BRCA1/2 pathogenic variant. We analyzed 2235 women with breast cancer who underwent BRCA1/2 genetic testing between 1996 and 2018 using data from the Japanese hereditary breast and ovarian cancer syndrome registry. The cumulative risk for contralateral and ipsilateral breast cancers and time to death since the first breast cancer were stratified based on the BRCA1/2 variant status. The median follow-up was 3.0 years (0.1-34.1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Therefore, the difference in the prevalence of each gene might be explained by genetic drift in the studied population or sampling bias due to the small number of participants. Among the 10 recurrently found g BRCA1/2 -PV (in more than 10 families) in the Japanese Organization Of Hereditary Breast and Ovarian Cancer (JOHBOC) registry in Japan [ 16 , 25 ], only three variants, BRCA1 :c.2800C>T, BRCA2 :c.6952C>T, and BRCA2 :c.9076C>T, were identified in our OC cases. In contrast, three g BRCA2 -PV, two of which were observed in more than one case, found in our study had not been identified in previous studies of Japanese cases with OC [ 6 , 7 ] and BC [ 16 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the difference in the prevalence of each gene might be explained by genetic drift in the studied population or sampling bias due to the small number of participants. Among the 10 recurrently found g BRCA1/2 -PV (in more than 10 families) in the Japanese Organization Of Hereditary Breast and Ovarian Cancer (JOHBOC) registry in Japan [ 16 , 25 ], only three variants, BRCA1 :c.2800C>T, BRCA2 :c.6952C>T, and BRCA2 :c.9076C>T, were identified in our OC cases. In contrast, three g BRCA2 -PV, two of which were observed in more than one case, found in our study had not been identified in previous studies of Japanese cases with OC [ 6 , 7 ] and BC [ 16 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 10 recurrently found g BRCA1/2 -PV (in more than 10 families) in the Japanese Organization Of Hereditary Breast and Ovarian Cancer (JOHBOC) registry in Japan [ 16 , 25 ], only three variants, BRCA1 :c.2800C>T, BRCA2 :c.6952C>T, and BRCA2 :c.9076C>T, were identified in our OC cases. In contrast, three g BRCA2 -PV, two of which were observed in more than one case, found in our study had not been identified in previous studies of Japanese cases with OC [ 6 , 7 ] and BC [ 16 , 24 ]. In addition, among these three variants, NM_000059.4:c.3703C>T (p.Gln1235*) and NM_000059.4:c.7922dup (p.Phe2642Ilefs*3) have never been reported previously, suggesting that these are novel pathogenic variants and some g BRCA2 -PV unique to the local area may exist in Tokushima prefecture located on the island of Shikoku, Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics and breast cancer subtypes were compared between carriers of BRCA2 c.5576_5579del and those of other PVs. The detection rate of BRCA2 c.5576_5579del in the BRCA1/2 genetic testing at each institution was also compared with that in the previous report [15].…”
Section: Methodsmentioning
confidence: 99%
“…We compared the BRCA1/2carrier frequency in patients among four hospitals. We also compared the frequency of PVs in the observed patients with that observed in Japanese patients reported by Yoshimura, et al [15]. We used a pie chart to compare the proportion of PVs at each hospital.…”
Section: Declarations Figuresmentioning
confidence: 99%
See 1 more Smart Citation